2019
DOI: 10.1126/sciimmunol.aau3814
|View full text |Cite
|
Sign up to set email alerts
|

RELMα-expressing macrophages protect against fatal lung damage and reduce parasite burden during helminth infection

Abstract: Alternatively activated macrophages (AAMs) can contribute to wound healing, regulation of glucose and fat metabolism, resolution of inflammation, and protective immunity against helminths. Their differentiation, tissue distribution, and effector functions are incompletely understood. Murine AAMs express high levels of resistin-like molecule (RELM) α, an effector protein with potent immunomodulatory functions. To visualize RELMα+ macrophages (MΦs) in vivo and evaluate their role in defense against helminths, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 47 publications
5
50
0
Order By: Relevance
“…In the absence of IL-13, CD45 -EpCAM + epithelial cells had significantly impaired expression of RELM- as early as D2pi and was still muted by D6pi when compared to WT controls ( Figure 5D). Consistent with previous findings (36,37), epithelial cells were the major source of RELM- at these time points whilst other cellular sources such as alveolar macrophages, neutrophils, and eosinophils, were relatively unchanged in the absence of IL-13 following infection (data not shown). As a complementary experiment, equimolar amounts of systemic IL-4 and IL-13 were each delivered by intraperitoneal injection into WT mice and 18 h later epithelial RELM- expression was measured in the lungs.…”
Section: Il-13 Is Required For Induction Of Epithelial Cell-derived Rsupporting
confidence: 92%
“…In the absence of IL-13, CD45 -EpCAM + epithelial cells had significantly impaired expression of RELM- as early as D2pi and was still muted by D6pi when compared to WT controls ( Figure 5D). Consistent with previous findings (36,37), epithelial cells were the major source of RELM- at these time points whilst other cellular sources such as alveolar macrophages, neutrophils, and eosinophils, were relatively unchanged in the absence of IL-13 following infection (data not shown). As a complementary experiment, equimolar amounts of systemic IL-4 and IL-13 were each delivered by intraperitoneal injection into WT mice and 18 h later epithelial RELM- expression was measured in the lungs.…”
Section: Il-13 Is Required For Induction Of Epithelial Cell-derived Rsupporting
confidence: 92%
“…Here we show that RELMα was expressed in some CD68+ macrophages as expected (presumably AA/M2 macrophages) but in addition CD68-cells in the parenchyma (Figure 2). Others have shown that RELMα can be expressed by alveolar type II epithelial cells using RELMα promoter reporter mice [40]. Thus, alveolar type II epithelial cells may also be responsive to OSM with RELMα expression (we have published that these cells express IL-33 in response to OSM in vitro and in vitro).…”
Section: Discussionmentioning
confidence: 65%
“…Most sources are consistent with these explanations, but nevertheless, there have also been reports stating that for example the AAM response is unsafe for helminths and instead, the parasite seeks to inhibit AAM production and accepts the production of classically activated macrophages (71). In fact, it has been shown that AAMs protect mice from secondary infections with H. bakeri (72) and N. brasiliensis (73). Nonetheless, more research is required to understand how AAMs regulate anti-helminth immunity and restore tissue integrity.…”
Section: Discussionmentioning
confidence: 98%